Volcanic tempo driven by rapid fluctuations in mantle temperature during large igneous province emplacement - Carter, Elliot J.; Stock, Michael J.; Beresford-Browne, Adam; Cooper, Mark R.; Raine, Robert; Fereyrolles, Alexia (Earth and Planetary Science Letters, 2024)
International audience The generation of Large Igneous Provinces (LIPs) is a topic of vigorous debate with competing models variably invoking hot mantle plumes, insulative heating by supercontinents or edge driven convective instabilities. Mantle temperature and its temporal variation during LIP magmatism is key to distinguishing between these different models. This may have important consequences for the dynamics, evolution and tempo of volcano-magmatic systems developed during these periods of intense activity. Despite this, there are currently no detailed stratigraphically constrained studies of mantle temperature through a LIP succession. To address this, we have applied both olivine-spinel thermometry and modelling of primary magma compositions (Monte Carlo PRIMELT3) to constrain mantle potential temperature through a continuous sequence of LIP lavas formed during the earliest expression of the North Atlantic Igneous Province (the Antrim Lava Group). Mantle potential temperature derived from olivine-spinel and olivine addition methods give consistent temperature ranges of 1403–1521 °C and 1374–1472 °C, respectively. However, both temperature records indicate significant (100–120 °C) variation in melting temperature over a relatively short stratigraphic interval during petrogenesis of early magmas and much less variation in later magmas, suggesting initial instability or pulsing which stabilised with time. This supports a plume origin for LIP formation. Variability in melting temperature is mirrored by proxies for crustal and volcanic processes; olivine Ni contents are elevated (<3000 ppm) in the same stratigraphic interval as the lowest mantle temperatures, indicating mixing of primary and more evolved (MgO ∼4 %) melts, resulting from low magmatic flux into the crust during this time interval. The abundance and thickness of red weathering horizons capping lava flows is also significantly higher through the succession where mantle temperature variation is highest, indicating prolonged repose periods ...